IMPLEMENTATION OF REST API ARCHITECTURE FOR FEELSQUEST ONLINE COURSE FEATURE IN FEELSBOX APPLICATION USING LARAVEL FRAMEWORK - Riawan, Faza Alexander; Kusumo, Dana Sulistyo; Selviandro, Nungki (Informatika, Universitas Jenderal Soedirman, 2024)
Feelsbox is a digital-based startup that focuses on the importance of mental health issues and offers innovative solutions to help people maintain their mental health. FeelsBox took the initiative to develop an online course feature